Effect Of Intravenous Magnesium Sulphate And Lidocaine Infusions On Intraoperative Haemodynamics And Muscle Relaxant Requirement In Functional Endoscopic Sinus Surgery (Fess) - Likitha, Kota; Darshini aarumulla, Shiny Priya; Swathi, Gundlakunta; Chaitanya, K. Krishna; Teja Reddy, . Avula Charan; Ishwarya, Williams Angela (Journal of Neonatal Surgery, 2025)
Background: FESS requires hypotension to decrease intraoperative bleeding for better visibility and to reduce duration of procedure. Controlled hypotension using agents like magnesium sulphate and lidocaine may improve outcomes. We compare intravenous magnesium sulphate and lidocaine infusion for maintaining intraop hemodynamics and its effect on muscle relaxant requirement and surgical field AIM: To compare the effectiveness of intravenous magnesium sulphate and lidocaine in achieving controlled hemodynamics and reducing muscle relaxant requirements in patients undergoing FESS. Methodology: The Institutional Ethics Committee of our college approved this randomized, prospective, double-blinded controlled study. A total of 80 patients scheduled to undergo Functional Endoscopic Sinus Surgery (FESS) were randomly allocated into two groups. Group L (n = 40) received intravenous lidocaine with a loading dose of 1.5 mg/kg followed by a maintenance infusion of 1.5 mg/kg/hour. Group M (n = 40) received intravenous magnesium sulfate with a loading dose of 40 mg/kg diluted in 100 mL of normal saline administered over 10 minutes, followed by a maintenance infusion of 15 mg/kg/hour. The primary outcomes were intraoperative hemodynamic parameters, specifically heart rate (HR) and mean arterial pressure (MAP), measured at 10-minute intervals, and the total muscle relaxant requirement. The secondary outcome was assessment of surgical field clarity, evaluated using the six-point Fromme and Boezaart scale by a surgeon blinded to the study groups. Results: Magnesium showed statistically significant difference in haemodynamics and surgical field visibility than lidocaine . Magnesium showed significant decrease in muscle relaxant requirement (p – 0.001) than lidocaine Conclusion: Magnesium sulphate maintained intra op hemodynamics and better surgical field visibility than lidocaine. Magnesium sulfate had a lower muscle relaxant requirement.